In the present looking back and imagining a future that could be - Segalo, Puleng (PINS-Psychology in Society, 2025)
Stevens, Garth, Duncan, Norman & Hook, Derek (eds) (2013) Race, memory and the Apartheid Archive: Towards a transformative psychosocial praxis. Houndmills: Palgrave Macmillan. ISBN 978-1-137-26389-6 hbk. Pages xviii + 368. Johannesburg: Wits University Press. ISBN 978-1-86814-756-4 pbk. 320 Pages. “Traumatic experiences from the past will constantly attempt to re-inscribe themselves (often in masked form) in the present, if they are not acknowledged, interrogated, and addressed.” (Apartheid Archive Project, 2010) They are considering giving him parole after only 20 years ... He has not even served a fraction of his sentence. Could they not wait for us to die first? Why are they opening the wounds? Is he celebrating 20 years of democracy too and being given freedom as a gift? What about our pain, our loss? (Paraphrased response from a family member of one of Eugene De Kock’s victims interviewed on eNCA News channel, 30 May 2014). Narrated in a blend of frustration and outrage, helplessness and betrayal, this plea delivers an unfinished story, wounds that continue to fester, perhaps re-opened with his release, and healing that is never quite complete. The Apartheid Archive, a virtual attic of such stories, reminds us that as a nation, and a world, tomorrow is never possible without revisiting yesterday; that healing is a national obligation, never resolved in a single act of reconciliation. With their plea, the family has brought to the public their hidden transcript of pain. I see this as a befitting opening to my reflection on the book that engages with the project of memory and the complexities of race within a country like South Africa. This book is a treasure and a burden, insisting that we remember and re-view, re-engage and reflect on the cost of ignorance, breaking the silence, and being in conversation with how our past influences the present. This volume insists that we integrate memory, pain and the unspoken into our vision for social justice.